Congenital sternoclavicular dermoid sinus. (February 2016) - Willaert, Annelore; Bruninx, Liesje; Hens, Greet; Hauben, Esther; Devriendt, Koen; Vander Poorten, Vincent
Abstract: We report a case series of 8 patients, presenting with a congenital sinus in the region of the sternoclavicular joint. This rare malformation has only been reported in the Japanese dermatological literature under the name of "congenital dermoid fistula of the anterior chest region". It has to be distinguished from other congenital anomalies and requires complete excision.